Android Corporeality, Transhuman Performance and the Japanese 'Mind'. (17th November 2018) - Sone, Yuji
Abstract : This essay examines Alter, an android that was developed collaboratively by Japanese roboticist Hiroshi Ishiguro and A-Life (artificial life) scientist Takashi Ikegami. Alter is an experimental robot platform conceived as a 'machine human'. Alter was created at the juncture of Ishiguro's interest in android appearance and Ikegami's search for what he sees as internal principles underlying life. While Ishiguro's anthropomorphic machines are intended as models for future humanoid robots in workplaces and domestic contexts, they are also intended as experimental tools for his investigations on human identity, the 'soul', and sociality, and related philosophical questions, such as 'What is the human?' In contrast, Ikegami works with a different question: 'What is natural life?' Ikegami's question emerges from his research interest in and development of artificial life systems, which combine computer simulation, chemical experiments, and robotics. Alter, presented as an interactive performance installation at a science museum in Japan in 2016, was intended as a model with which to study human embodiment and sentience. In this essay, I examine how Alter's 2016 performance was designed dramaturgically to induce a sense of agency hovering between the organic and the inorganic, the natural and mechanical, the random and controlled, and between the autonomous and programmed. I discuss how Alter rehearsed human-machine inter-corporeality, and how its dramaturgical staging contributed to its agency.